2009
DOI: 10.1590/1809-9823.2009.00013
|View full text |Cite
|
Sign up to set email alerts
|

Fatores que predispõem ao declínio funcional em idosos hospitalizados

Abstract: Introduction: The increase in life expectancy is a global reality and determines the highest prevalence of chronic diseases and greater demand for health services, including hospitals. Currently, studies have focused on functional decline and its consequences -the demand for material and human resources, institutionalization and hospitalization. This paper aimed to critically review the available literature on the risk factors associated with functional decline in hospitalized elderly people. Methodology: Sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
13

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 26 publications
0
14
0
13
Order By: Relevance
“…Functionality reduction is estimated to reach from 34% to 50% of older people during hospitalization 3,16 . A literature review showed depression, delirium, cognitive and physical impairment, environmental factors, prior functional incapacity, and polypharmacy as risk factors for functional decline in hospitalized older people 17 . Such information reinforces our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Functionality reduction is estimated to reach from 34% to 50% of older people during hospitalization 3,16 . A literature review showed depression, delirium, cognitive and physical impairment, environmental factors, prior functional incapacity, and polypharmacy as risk factors for functional decline in hospitalized older people 17 . Such information reinforces our findings.…”
Section: Discussionmentioning
confidence: 99%
“…A realização da avaliação de declínio cognitivo é importante para tracejar os fatores de risco, bem como apontar os grupos mais acometidos 14 . Como mostram pesquisas correlacionando fatores individuais, as obras estudas tem em comum a relação de declínio cognitivo ser maior entre as mulheres 4,14,18 . Entretanto o fator idade cultuado como precursor do declínio, não foi unanime nas literaturas estudadas, como pode-se observar Machado et al 14 , aponta maior índice entre a população de 60 a 69 anos.…”
Section: Discussionunclassified
“…Lourenço et al 18 , relata que indivíduos acima de 80 anos eram 23.1% mais acometidos com o declínio. Contudo Cunha et al 4 , emprega que idade não é relevante, sendo o quadro patológico de maior interesse, ou seja, a piora clinica faz evoluir o declínio cognitivo.…”
Section: Discussionunclassified
See 2 more Smart Citations